Morphogenesis of bursa of Fabricius in chick - Verma, D; Malik, M R; Parmar, M L; Taluja, J S (The Indian Journal of Animal Sciences, 2012)
The study was conducted in 18 prehatch and 42 posthatch normal chicks of White Leghom (WLH) birds divided into 10 groups of 6 birds each. Bursa of Fabricius was conspicuous at day 12 of incubation and resembled the size of a mustard seed. It increased in size from day 12 of incubation to 8 weeks of age and started involuting in the chicks of 8 weeks onward. It measured 3.20 and 3.00 mm at day 12 of incubation and 18.12 and 11.64 mm in the chicks of 8 weeks of age in length and width respectively. The length decreased 57.97% in the chicks of 16-32 weeks of age and width 13.74% in 8-16 weeks and 0.30% in 16-32 weeks of age. The capsule over bursa of Fabricius was made up of dense collagenous tissue at day 12 and 19 of incubation, fibromuscular in day-old chick and increased 3 times in thickness at 2 weeks of age. The epithelium lining the folds was pseudostratified at day 12 and 19 of incubation but differentiated into simple columnar in older chicks. The bursal folds were club-shaped, enlogated and pyramidal at day 19 of incubation and increased in height from day 19 of incubation to 32 weeks of age. In day-old chick the folds were divided by deep indentation to form secondary folds. The lymphatic nodules separated by connective tissue at 19 day of incubation got involved with the advancement of age.